METAMORFOSA WAJAH KURIKULUM: Sejarah Perkembangan Acuan Pendidikan di Indonesia - Fahyumi Rahman (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2021)
The curriculum transformation started from before independence, where its existence was still under the Dutch of colonial authority. The design and implementation of education were only to oriented to the interests of colonial colonialism. When Indonesia's independence was proclaimed in 1945, the entire system in Indonesian was reconstructed, including in the field of the education. The change in the curriculum was caused by several factors, including irrelevance for the national goals, government of policies, and the projections of future human resource needs. The aims of paper is to retrospect on the curriculum development in order to answer or reconstruct of educational curriculum in the future. That is important in to seeing to influence of the curriculum on the direction of national development. This paper uses literature study by exploring library sources and packaged in descriptive analysis. The results obtained from this paper are that the Leerplan curriculum is the beginning of the education curriculum in Indonesia, which is still simple in shape. The development of the New Order government to the old order, curriculum changes experienced a significant increase, especially to carry out the ideals of the Constitution and Pancasila. And then, the curriculum in the reform era, the uniqueness of the curriculum at this time, is starting to explore the skills that are input on the educational foundation, refined again in the competency-based curriculum phase, KTSP and then K13.